(untitled) (Canadian Journal of Native Studies, 2026)
This article explores how food is connected to health, not only by the physical body but through a connection to our culture, our community, our ancestors, and the earth. Establishing food security and sovereignty – access to traditional foods and control over food supply – is crucial to decolonization and healing for Indigenous people. This article combines teachings from Elders with insights from an Indigenous chef about how food can heal. It takes the reader on a culinary journey through a heart-warming event “Community Kitchen: Food, Medicine and Memories” held by the First Nation House at the University of Toronto.